In praise of ambidexterity: How a continuum of handedness predicts social adjustment - Kevin Denny; Wen Zhang (University College Dublin, UCD School of Economics, 2010)
This paper estimates the relationship between handedness and social adjustment. In addition to binary measures of hand preference, we also use a continuous measure of hand skill. Outcomes at ages 7, 11 and 16 are studied. Using a semi-parametric estimator it is shown that non-righthandedness (as hand-preference) is associated with poorer social adjustment but this effect disappears as the individuals age. The continuous measure of hand skill has a non-monotonic effect on social adjustment with poorer social adjustment at the extreme values of the continuum. Poorer social adjustment in childhood has been shown to predict poorer socio-economic outcomes later in life.
hdl:10197/2634
Keywords: 330